PEMANFAATAN LIMBAH KULIT JAGUNG DAN CANGKANG TELUR UNTUK BAHAN BAKU MASKER PEEL-OFF - Priska Meliawati, Wa Ode; -, Nurhayati (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
According to research, corn husk waste contains alkaloid compounds with antioxidant activity of 43.13% which functions to increase collagen production, reduce fine lines and wrinkles, reduce black spots and treat acne. Meanwhile, the eggshell membrane contained in eggshells contains collagen and protein which can help rejuvenate the skin and increase skin elasticity. Utilizing the potential of organic waste corn husks and eggshell membranes as a source of antioxidants and collagen for raw materials for skin care cosmetics has advantages in terms of economics and environment. Because it can reduce waste generation, it can also be economically profitable. The aim of this research was to determine the physical quality of a peel-off mask made from corn husk extract and eggshell membrane powder. As well as identifying antioxidant activity and collagen mask content in peel-off masks. Peel-off masks from these two materials meet the physical quality test for peel-off masks. With a pH ranging from 6.5-6. Spreadability between 4.2-5.5 cm. Drying time ranges from 14-24 minutes. The IC50 value of the peel off mask is 7785.87 ppm which shows that there is no antioxidant potential in the product. Identification of collagen using the FTIR method indicates the presence of a secondary structure of â-sheet protein which shows that the existing collagen has not been degraded into gelatin